Enhancing the Digital Literacy of Bank NTT Customers in Protecting Personal Data Against Cybercrime Threats - Susilawati, Made; Long, Maria Lodika (International Ecsis Association, 2025)
The growth of digital banking has reshaped customer interactions with financial institutions, offering greater convenience yet simultaneously exposing users to new forms of cyber risk. This research explores how digital literacy, perceived ease of use, and digital literacy education influence customers’ awareness of personal data protection, while also identifying effective approaches to strengthen cybersecurity awareness among Bank NTT’s clients. A mixed-method design was employed, combining quantitative surveys with in-depth qualitative interviews to capture both measurable patterns and contextual insights. Statistical analyses, including reliability, correlation, and multiple regression tests, were complemented by thematic analysis of interview data to reveal behavioral tendencies and cognitive perceptions related to digital safety. The findings highlight that higher levels of digital literacy substantially enhance customers’ understanding and awareness of data security. Moreover, perceptions of ease and usefulness of digital banking services, along with consistent digital literacy education, foster more preventive and responsible online behaviors. Experiences of or exposure to cybercrime incidents were also found to strengthen customers’ motivation to safeguard their personal information. Overall, this study emphasizes that building cybersecurity awareness in the banking sector requires continuous digital education, user-oriented service innovation, and practical learning experiences to cultivate a culture of data protection and trust in digital financial ecosystems.